2023
DOI: 10.1007/s12288-023-01651-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Frequency and Specificity of Red Cell Antibodies in Patients with Hemoglobinopathies

Abstract: Patients with thalassemia and sickle cell disease (SCD) require blood transfusions as part of their supportive care. However, one of the most serious side effects of this treatment is the risk of red cell alloimmunization. The goal of this study was to assess the prevalence and Specificity of red cell alloimmunization in Egyptian thalassemia and sickle cell anaemia patients. This study included 200 multi transfused Egyptian patients, one hundred and forty patients with transfusion dependent thalassaemia and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…A recently cohort study reported that a total of 27 alloantibodies with 9 specificities were identified in both sickle cell anemia and thalassemia patients. The most frequent alloantibodies in thalassemia patients were anti-K (47%) followed by anti-E (23.5%) 26 . A similar study conducted in Egypt by Osman et al discovered that anti-K (37.3%) and anti-E (34.3%) were also the most prevalent alloantibodies in thalassemia patients 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently cohort study reported that a total of 27 alloantibodies with 9 specificities were identified in both sickle cell anemia and thalassemia patients. The most frequent alloantibodies in thalassemia patients were anti-K (47%) followed by anti-E (23.5%) 26 . A similar study conducted in Egypt by Osman et al discovered that anti-K (37.3%) and anti-E (34.3%) were also the most prevalent alloantibodies in thalassemia patients 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Female gender is a significant independent risk factor for alloimmunization, particularly for those who may become pregnant or give birth in the future. As a result of previous alloimmunization, these patients may also have a higher incidence of hemolytic disease in their newborns 26 .…”
Section: Discussionmentioning
confidence: 99%